Indeksy eritrocitov v ocenke adaptacionnych reakcij organizma vysokokvalificirovannych sportsmenov Jakutii - Semenova, E. I.; Mironova, G. E.; Krivoshapkina, Z. N.; Olesova, L. D.; Efremova, A. V.; Konstantinova, L. I.; Yakovleva, A. I.; Grigorieva, A. A. (Theory and Practice of Physical Culture, 2018)
The highly-skilled Yakut athletes have to live and train in the extreme climatic conditions of the Russian Far North and, therefore, their training process needs to be supported by accessible and dependable express test methods to control their adaptation processes. Some researchers recommend a variety of morpho-functional rating criteria to profile their body responses to stressors. The study was designed to measure the erythrocyte indices in highly-skilled Yakut athletes (n=169) including freestyle wrestlers (n=112) and boxers (n=57) aged 18-28 years. It was found that the specific (per 1 mcl) variations of hemoglobin, hematocrit, erythrocyte indices (MCV, MCH, MCHC) in the Yakut athletes are sport- and training-stage- specific. The expressed variations of the blood profiles versus the standard in some athletes in the preseason period may be interpreted as indicative of the drawbacks in the preseason weight loss systems. The expressed sag of the HGB and HCT rates in the boxing subsample may be indicative of the hypochrome anemia due to the specific requirements of the competitive process. The growth of erythrocyte indices (MCH, MCHC) in some athletes, particularly in the preseason period, may be indicative of the tissue-level hypoxia and dehydration. The MCV growth commonly associated with the thickening of the erythrocyte membrane and spherical index variation may be interpreted as the bodily adaptation to the water-electrolyte balance in blood under hypotonic type. These adaptability conditions were found to be of limiting effect on the athletes` physicality including the endurance and physical working capacity rates and, hence, on their competitive success rates.